Geomorphological Mapping of the gully erosion in the Brazilian Cerrado using Remotely Piloted Aircraft (RPA) - Mizumura, Willian Toshiaki; Silveira, Alan; Petronzio, Juliana Abreu Crosara; Andrade, Samuel Lacerda de; Silva, Valdiney José da (Revista Brasileira de Geomorfologia, 2025)
Detailed geomorphological mapping employs imagery acquired by Remotely Piloted Aircraft (RPA) to investigate gullies, generating morphometric data. This study aimed to develop a detailed geomorphological map, defining geomorphological compartments and recording discrete landform features both within and around the gully, using traditional and adapted symbology. The study area corresponds to the Mombuca Gully in the Brazilian Cerrado, at Monte Carmelo (Minas Gerais, Brazil). The methodology was divided into pre-field, field, and post-field stages, encompassing flight planning; image acquisition with the DJI (Da-Jiang Innovations) Mavic Pro RPA in three scenarios; image treatment, processing, and photo-interpretation to generate morphometric and geomorphological maps. The study identified five geomorphological compartments and documented denudational features, aggradational features, anthropogenic landforms, technogenic deposits, alterations of original channel courses, and the installation of impoundments. Integrated analysis of these data enabled an understanding of natural erosive dynamics and anthropogenic influences. The results support methodological discussions on geomorphological mapping of gullies using high-resolution imagery.